Kesejahteraan Karyawan pada PT. Karya Tanah Subur dalam Mendapatkan Keselamatan dan Kenyamanan dalam Bekerja - Ola, Cut; Nisrina, Dhia; Abdul Manan, Afni; Morisna, Titin (Teewan Journal Solutions, 2025)
The purpose of this research is to find out how a company innovates in carrying out its obligations to guarantee the safety of employees and employees' families to be more prosperous, so that employees and companies provide mutual feedback/reciprocal relationships between workers and the company. This case study was carried out at PT. Karya Tanah Subur Padang Sikabu. This research was conducted by interviewing staff in the Human Resource Development (HRD) section of PT. Padang Sikabu Fertile Land Works. This analysis was carried out in order to find out how the company PT. Karya Tanah Subur is taking steps to improve the welfare of the employees who work at this agency. The results from the researchers found that the company's innovation and concern for its employees was very good